2017
DOI: 10.1097/mib.0000000000001148
|View full text |Cite
|
Sign up to set email alerts
|

Combined Detection of NUDT15 Variants Could Highly Predict Thiopurine-induced Leukopenia in Chinese Patients with Inflammatory Bowel Disease

Abstract: We confirmed that NUDT15 c.415C>T, c.36_37insGGAGTC, and c.52G>A variants were risk factors for thiopurine-induced leukopenia. Combined detection of the 3 variants could increase the predictive sensitivity of thiopurine-induced leukopenia and help to distinguish early leukopenia in heterozygote of c.415C>T in Chinese patients with IBD. Treatment monitoring by NUDT15 variants may be promising in individualized therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 27 publications
11
79
0
Order By: Relevance
“…The association of TPMT genotype polymorphisms and TIL was assessed in 31 studies, the association of TPMT enzymatic activity and TIL in 12 (Table S1). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The association of TPMT genotype polymorphisms and TIL was assessed in 31 studies, the association of TPMT enzymatic activity and TIL in 12 (Table S1). …”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were identified that evaluated NUDT15 variants as risk factors for TIL in IBD patients, one also described the association of NUDT15 activity and TIL (Table S3). The majority of studies were performed in East‐Asian cohorts, one study included only patients of European ancestry . Studied NUDT15 variants were NUDT15 R139C (rs116855232) in 13 studies, NUDT15 c.36_37ins/delGGAGTC (rs746071566) in six studies and c.52G > A (rs186364861) in four studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 3‐14% of patients possess one variant allele of thiopurine methyltransferase . In a recent report, 24.2% of Chinese Han patients with IBD experienced leukopenia when using thiopurine and adverse events were related to NUDT15 variants . Another report showed that heterozygous and homozygous variant NUDT15 p.Arg139Cys alleles were found in 21.9% and 5.0% of Japanese IBD patients, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…26 In a recent report, 24.2% of Chinese Han patients with IBD experienced leukopenia when using thiopurine and adverse events were related to NUDT15 variants. 27 Another report showed Although some studies on rheumatoid arthritis have excluded age as a predictive factor for the effects of MTX treatment, [30][31][32] no studies, to our knowledge, have evaluated both age and MTX efficacy in patients with IBD. Regardless of the small sample size, we found that those who failed to maintain remission were elder than those who maintained remission after MTX treatment.…”
Section: Discussionmentioning
confidence: 99%